A Note on Soviet Pricing, Profits and Technological Choice - Aberg, Morgan; Persson, Hakan (Review of Economic Studies, 1980)
Morgan Åberg, Håkan Persson; A Note on Soviet Pricing, Profits and Technological Choice, The Review of Economic Studies, Volume 47, Issue 3, 1 April 1980, Pages